Evolution of insulin production technologies: from historical discoveries of the molecule structure to modern innovations - Kaliuzhnaia, Olha; Khokhlenkova, Natalya (ScienceRise: Biological Science, 2025)
The aim of the study is to assess the current state of the pharmaceutical market for insulins, including historical stages of studying the structure of the insulin molecule and its properties, which formed the basis for the development of commercial preparations and analogs, as well as analysis of promising biotechnological approaches to improve the treatment of diabetes mellitus (DM). Materials and methods. The materials used were scientific publications, official websites of manufacturing companies, FDA and EMA databases, clinical trial registries. Methods of content analysis, comparative, analytical, and generalization of information were applied. Results and discussion. The results indicate that recombinant insulin preparations (from rapid-acting analogs to long-acting ones) provide better glycemic control but are limited by high development and production costs. Innovations include combined preparations with GLP-1 agonists, glucose-sensitive insulins, and oral forms, which face bioavailability challenges. Conclusions. The analysis points to the evolution of insulin production technologies from determining the molecule structure and implementing recombinant DNA technologies, which enabled the transition to human recombinant preparations and analogs. The market offers preparations with various profiles (from ultra-rapid to ultra-long), including biphasic mixtures, improving glycemic control. Combinations of insulin with GLP-1 agonists, amylin analogs (pramlintide), and the development of glucose-sensitive insulins have potential for personalized therapy but are limited by technical challenges (stability, biocompatibility). Oral forms face low bioavailability, but the use of nanotechnology and effective excipients opens prospects for improving accessibility and effectiveness of DM treatment